Програмне забезпечення зі збереження, організації та керування закладками з використанням штучного інтелекту - Мякшин, А. С. (ХНУРЕ, 2024)
This work is devoted to the development of software for bookmark management using artificial intelligence. The main goal of the research is the introduction of new functionality based on the analysis of modern products on the market, as well as the use of artificial intelligence to increase interactivity and expand capabilities. The following methods were used to conduct the research: comparative analysis of existing solutions, analysis of user requirements, selection of technologies, implementation and testing of the product. The result of the research was cross-platform software, the functionality of which allows users to create their own working environment for managing bookmarks, as well as actively interact with their content using artificial intelligence capabilities
Keywords: керування закладками; ресурс Закладка»